THE RELATIONSHIP BETWEEN CLEAN AND HEALTHY LIVING BEHAVIOR KNOWLEDGE AND SCABIES PREVENTION IN CHILDREN - Asri Kusyani (Universitas Negeri Surabaya, 2025)
Scabies or also known as scabies, gudig, and budug, is a skin disease caused by infection with the Sarcoptes scabiei mite variety hominis. Scabies is often ignored by society, this often occurs due to poor personal hygiene habits, and lack of knowledge. The purpose of this study is to analyze the relationship between knowledge about clean and healthy living behaviors and the prevention of scabies in children at MI Miftahul Ulum Blaban Batumar-mar, Pamekasan Regency, Madura. This research method uses correlation analysis with a cross-sectional approach. The population of Mi Miftahul Ulum Blaban Batumar-mar Pamekasan is 50 students. The study sample is 50 people selected as a whole. using the total sampling technique. The results of the study show Sig. value 0.000, so there is a Relationship between PHBS Knowledge and Scabies Prevention at MI Miftahul Ulum Blaban, Batu Mar-Mar District, Pamekasan Regency, Madura. Knowledge about clean and healthy living behaviors greatly affects the incidence of scabies. The higher the knowledge about clean and healthy living behaviors, the lower the risk of contracting diseases, one of which is scabies.